First Report on Apothecium Deformity of Morchella importuna Caused by Alternaria alternata in China - Wei, Yingfan (Plant disease, 2024)
Morel mushrooms (Morchella spp.) are highly regarded globally for their distinctive texture and savory flavor. In 2022, the cultivation area for morel mushrooms in China reached nearly 20,000 hectares, with predominant cultivars including M. sextelata, M. importuna and M. exima (Bian et al., 2024). In March 2022, however, deformities of friting bodies were observed in M. importna at morel mushroom farms in Huaihua city (28.43°N, 110.47°), China, with an incidence rate ranging from 5% to 10%. The disease symptoms begin with the invasion of the hymenium of morel mushroom by white cotton-like mycelia, ultimately resulting in halted fruiting body growth and the manifestation of anomalous fruiting body morphology. Infected samples were collected from the morel growers. Following sterilization with 75% ethanol of the surrounding tissue of infected samples, the white hyphae from the morel lesions were picked out using a dissecting needle, and incubated onto potato saccharose agar medium supplemented with 60 mg/L streptomycin at 25°C. Studies showed that seven out of nine fungal isolates exhibiting identical morphological features rapidly grew on the same culture medium described above, reaching a length of 75 mm in 4 to 5 days at 25°C. The white and thick hyphal colonies of these isolates gradually filled with brown spore powder. Generally, the conidia of the hyphal colonies were polyblastic with protrusions at the tips, measuring 75 to 165 × 36 to 50 μm (n = 30) in width and length, displaying colors varying from light reddish brown to grayish brown, and possessing one or five septa. To confirm the identity of the pathogen, the region of the internal transcribed spacer region (ITS), 28S nuclear ribosomal large subunit (LSU), and RNA polymerase II second largest subunit (rpb2) genes of the representative isolate H2 were amplified by PCR (Taguiam, et al. 2021). The generated ITS (OR338304), rpb2 (OR452112) and LSU (OR338334) from the isolate H2 had 98-100% similarity to the Alternaria alternata strains ATCC 6663 and CBS 880.95 in BLASTn analysis. ITS, rpb2 and LSU sequences were assembled using Sequence Matrix, and their homogeneity was assessed with PAUP (Vaidya et al., 2011). Bayesian (MrBayes-3.2.7a) and maximum-likelihood (RAxML1.3.1) methods, utilizing the best fit GTR+G+I model obtained from MrModeltest 2.3, were employed for phylogenetic analysis (Aveskamp et al. 2010). Based on morphological characteristics and phylogenetic analysis, the isolate H2 was identified as A. alternata. In the second year post-disease, disease-free morels, with a height of 3 cm, were cultivated in field greenhouses and used for test. A 15 ml suspension (1 × 106 conidia/ml) was applied to 15 young fruiting bodies and their corresponding substrate soil. The results showed that the reappearance of white cotton-like mycelia and deformed M. importuna fruiting bodies within 7 days post-inoculation with the spore suspension, as opposed to the controls. The isolates (H2-1, H2-2 and H2-3) were reisolated from the infected tissues and identified as A. alternata based on its morphological features and phylogenetic analyses. In this study, a similar investigation was previously conducted on cultivated quinoa (Chenopodium quinoa) in Eastern Denmark (Colque-Little et al., 2023). This study marks the first documentation of A. alternata causing deformities in M. importuna fruiting bodies. These deformities occur under conditions of high-temperature (>22°C) and high humidity (>88%). Our findings provide crucial insights for managing A. alternata in M. importuna cultivation in China